Avaliação de método alternativo ao uso de antimicrobianos em diluentes de sêmen suíno e do impacto de antimicrobianos na microbiota endometrial e no desenvolvimento embrionário - Camargo, Janine de (2025)
Artificial insemination (AI) in the swine industry widely uses antimicrobials (ATB) in semen extenders to control bacterial contamination. However, this practice raises concerns about antimicrobial resistance, and its effects on the uterine environment and embryonic development remain poorly understood. This thesis aimed to: 1) evaluate the efficacy of a blister pack with a bacteriostatic coating as an alternative for storing swine semen; and 2) investigate the impact of using ATB in the insemination dose on the endometrial microbiota and initial embryonic development in female swine. For the first objective, in vitro assays were conducted to evaluate semen quality and bacterial growth, and field trials were performed to assess reproductive performance. Semen quality and bacterial growth were evaluated in blisters with and without a bacteriostatic coating, with and without ATB. Reproductive performance was evaluated in a commercial trial with 2,192 females. For the second objective, 15 gilts were inseminated with semen either containing (With ATB group) or not containing (Without ATB group) antimicrobials. Five days after AI, endometrial biopsies were collected for 16S rRNA gene sequencing and microbiota characterization, and the recovered embryos were classified according to their developmental stage and embryonic quality and stored for DNA methylation analysis. The results showed that the bacteriostatic blister effectively controlled bacterial growth, with counts comparable to the ATB controls (below 2 log10 CFU/mL), and maintained sperm quality, without negatively affecting the farrowing rate and the number of piglets born in the commercial trial. The investigation into the impact of ATBs revealed an alteration in the endometrial microbiota. The Without ATB group showed greater species richness (alpha diversity). Biomarker analysis (LEfSe) identified the phyla Actinomycetota and Pseudomonadota as characteristic of the With ATB group, while Bacillota and Spirochaetota were more abundant in the Without ATB group. Furthermore, the use of ATB was associated with a delay in the kinetics of embryonic development. The With ATB group showed a significantly higher proportion of embryos at the pre-morula stage and a lower proportion at the morula stage compared to the Without ATB group (p < 0.05), altering the kinetics of early embryonic development. At the molecular level, the alterations in embryonic DNA methylation found in the ATB group may impact the litter phenotype. In conclusion, the use of antimicrobials in the semen extender modulates the female endometrial microbiota and is associated with a delay in early embryonic development and epigenetic alterations. The blister with a bacteriostatic coating proved to be a safe and viable alternative, preserving semen quality and ensuring reproductive performance, representing an advancement towards more sustainable practices in swine production.